Seeking security in the dragon's shadow : China and Southeast Asia in the emerging Asian order - Acharya, Amitav (2009)
This paper examines China's changing security relations with Southeast Asia. It begins by highlighting the growing complexity of the relationship, marked by conflicting pulls of cooperation and rivalry. This is followed by case studies of the South China Sea dispute and the extent of the economic competition between China and Southeast Asia. The paper then assesses Chinese power projection capabilities in Southeast Asia, identifying its scope and limitations. The final section looks at strategies adopted by ASEAN members to "engage" China, especially through regional institutions such as the ASEAN Regional Forum and ASEAN Plus Three. The main argument of the paper is as follows. China's relations with Southeast Asia hav been, and will continue to be marked by a mix of competition and collaboration. In the short-term, ASEAN staes will seek to accomodate China and try to benefit from economic linkages with China's booming economy. At the same time, China's rising power will remain a concern, and ASEAN will seek avenues for dealing with a security challenge from China through a mix fo deterrence and cooperative security approaches. The key drivers for the long-term relationship, aside from China's domestic evolution, are the nature of Sino-US rivalry, the structure of regional economic interdependence, and the evolution of cooperative security norms in the region. Southeast Asia can have some role in shaping the last two forces, but this requires greater unity and sense of purpose in ASEAN than has been evident since 1997 Asian economic crisis.